2022
DOI: 10.1126/scitranslmed.abn2231
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic virus–mediated expansion of dual-specific CAR T cells improves efficacy against solid tumors in mice

Abstract: Oncolytic viruses (OVs) encoding a variety of transgenes have been evaluated as therapeutic tools to increase the efficacy of chimeric antigen receptor (CAR)–modified T cells in the solid tumor microenvironment (TME). Here, using systemically delivered OVs and CAR T cells in immunocompetent mouse models, we have defined a mechanism by which OVs can potentiate CAR T cell efficacy against solid tumor models of melanoma and glioma. We show that stimulation of the native T cell receptor (TCR) with viral or virally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 55 publications
0
57
0
Order By: Relevance
“…On the other hand, OVs penetrates into the tumor cells to replicate and lyse tumor cells and trigger an immune response that facilitates CAR-T cell attacks on surviving tumor cells. Intravenous administration of OV-loaded CAR-T cells showed good efficacy in mouse melanoma and glioma tumor models, with improved survival [98] . This study provides an innovative approach to the treatment of solid tumors with OVs in combination with CAR-T cells.…”
Section: Therapeutic Strategy Of Ovsmentioning
confidence: 99%
“…On the other hand, OVs penetrates into the tumor cells to replicate and lyse tumor cells and trigger an immune response that facilitates CAR-T cell attacks on surviving tumor cells. Intravenous administration of OV-loaded CAR-T cells showed good efficacy in mouse melanoma and glioma tumor models, with improved survival [98] . This study provides an innovative approach to the treatment of solid tumors with OVs in combination with CAR-T cells.…”
Section: Therapeutic Strategy Of Ovsmentioning
confidence: 99%
“…Although there are strong scientific rationales and preclinical evidence that support the combination of OV with CAR-T cells to induce synergistic antitumor efficacy, there are growing evidence that contrarily demonstrate that OV-induced type I IFN response can be detrimental to the functionality of T cells, including CAR-T cells, and induce their apoptotic cell death ( 48 , 247 , 248 ). One promising strategy to circumvent this issue is to infect the CAR-T cells directly with OVs which enables systemic delivery of both CAR-T cell and OV to solid tumors ( 249 ). In detail, dual-specific CAR-T cells that recognizes viral antigens of the OVs and EGFR of tumors infected with oncolytic reovirus or vesicular stomatitis virus (VSV) exhibited augmented proliferation and biological function due to stimulation of native T cell receptor by viral epitopes.…”
Section: Ov In Combination Therapy Regimenmentioning
confidence: 99%
“…Infected tumor cells with an oncolytic vaccinia virus coding for CD19t (OV19t) produces de novo CD19 at the cell surface and subsequent virus-mediated tumor cytolysis ( 68 ). Recently, another OV study revealed that induction of the native TCR with viral or virally encoded epitopes enhances CAR T cell proliferation, activity, and efficacy in mice with intracranial GBM tumors ( 69 ).…”
Section: Additional Chemical and External Treatmentsmentioning
confidence: 99%